Peran Sistem Informasi Manajemen dalam Pengambilan Keputusan di Madrasah Ibtidaiyah Darussalam Pacet Mojokerto - Akhmad Sirojuddin; Khus Amirullah; Muhammad Husnur Rofiq; Ari Kartiko (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This article aims to describe: 1) explain the management of the Management Information System, 2) explain the decision making based on data in the Management information system. This research is a qualitative descriptive study. Data was obtained through observation, interviews, and documentation. All collected data were then analyzed using data in a few stages from reducing data, presenting data, to drawing evaluation conclusions. Research informants were the Headmaster of MI Darussalam, the School operator, and Teachers. The results showed that. The Role of Management Information System in Decision Making in MI Darussalam: (1) The components in the Management Information System has been fulfilled, (2) management of management information systems centered on two people, (3) The flow of MIS management in MI Darussalam is the process of data input, data processing, and data storage, (4) The head of the Madrasah puts forward the principle of deliberation to make decisions. (5) The Management Information System is used as a database for making decisions and making program activities. (6) There is a Decisive Support System (DSS) that is used, but it is still constrained.